PENGARUH ECONOMIC VALUE ADDED(EVA)DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM SYARIAH - Nana Umdiana; Jenisya Jenisya (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2016)
ABSTRACT             This research aims to find out the influence of economic value added (EVA) and Net Profit Margin (NPM) towards stock price partially although simultaneously. Sample used are 10 companies listed on Jakarta Islamic Index period 2010-2014. The sampling technique used purposive sampling methods. Type of data is secondary data and data analysis methods are used multiple regression analysis by testing classical assumptions, and using t test and F test. The research shows that partially EVA have no a significant influence on stock price. While NPM partially have a significant influence on stock prices Simultaneously EVA and NPM have a significant influence on stock prices. Keywords :      Economic Value Added (EVA), Net Profit Margin (NPM),and Stock Price